Sayyid ʻAbd al-Raḥmān al-Mahdī a study of neo-Mahdīsm in the Sudan, 1899-1956 - Ibrahim, Hassan Ahmed (Islam in Africa, 2004)
This is an engrossing analysis of ʿAbd al-Raḥmān al-Mahdī's initiative to abandon the futile political violence and religious fanaticism of the 19th century historic Mahdiyya. It articulates his alternative constitutional strategy that has placed Neo-Mahdism in the centre stage of Sudanese politics.